Zakat Produktif Dalam Keberhasilan Usaha Mustahiq Ditinjau Dari Indikator Peningkatan Modal, Peningkatan Pendapatan, Peningkatan Jumlah Konsumen, Peningkatan Produksi dan Peningkatan Amal Jariyah Mustahiq (Studi Kasus LAZ Inisiatif Zakat Indonesia Cabang Jawa Timur) - Rachmat Darmawan; Sunan Fanani (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
This study aims to analyze the role of productive zakat managed by LAZ IZI, which has a role in increasing the success of mustahiq businesses in the city of Surabaya. There are five standards that can be used to measure the increase in business success of mustahiq, namely the standard of increasing capital, increasing income, increasing production, increasing the number of consumers and charity jariyah mustahiq. This study uses a qualitative approach with a case study method. The technique of collecting data uses direct interviews, documentation and observation. The analysis technique used is narrative-descriptive analysis. Then to find out the validity of the data, the researcher used the triangulation technique by cross checking the findings of primary data and secondary data. The results of this study were that the three informants experienced an increase in capital, an increase in income, an increase in production, an increase in the number of consumers and an increase in charity after receiving assistance. The informants felt the business they had run had success. The success of the informant's business can be seen from the increase in all indicators mentioned. Supervision and mentoring carried out by LAZ IZI Surabaya was felt very useful in motivating and encouraging continuous effort. In addition, they are able to set aside a portion of the assets to be given to those who are entitled.Keywords: Productive Zakat, Mustahiq, Utilization, Business Success